2018
DOI: 10.1007/s12640-018-9930-2
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid Is Highly Associated with Epilepsy Secondary to Cerebral Infarction

Abstract: In this study, we examined the association between serum uric acid levels and epilepsy secondary to cerebral infarction. Clinical data including age, gender, epileptic seizure type, imaging, and serum uric acid levels before and after seizures in patients with cerebral infarction that were collected and analyzed. One hundred patients with cerebral infarction but without epilepsy, 147 patients with epilepsy secondary to cerebral infarction, and 55 patients with status epilepticus secondary to cerebral infarctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…What is more, many laboratory findings like urine leukocytes, uric acid, alanine aminotransferase, creatine kinase and lactate dehydrogenase were also found to be associated with PSE. Uric acid is now believed to be inflammatory and has been confirmed by previous clinical and basic researches that both increase and decrease of uric acid level could lead to an increased incidence of PSE [25,26]. But the association between other laboratory findings and PSE need further research.…”
Section: Discussionmentioning
confidence: 92%
“…What is more, many laboratory findings like urine leukocytes, uric acid, alanine aminotransferase, creatine kinase and lactate dehydrogenase were also found to be associated with PSE. Uric acid is now believed to be inflammatory and has been confirmed by previous clinical and basic researches that both increase and decrease of uric acid level could lead to an increased incidence of PSE [25,26]. But the association between other laboratory findings and PSE need further research.…”
Section: Discussionmentioning
confidence: 92%
“…A complex relationship has been reported between SUA and epilepsy. SUA levels greater than 322 μmol/L or less than 248 μmol/L have been associated with an increased risk of developing epileptic seizures after cerebral infarction compared to SUA levels of 248-322 μmol/L, indicating a U-shaped dose-effect relationship between the SUA level and epilepsy after cerebral infarction [19]. A previous study reported that treatment with carbamazepine and phenytoin was related with low SUA levels, and phenobarbitone and sodium valproate were associated with elevated SUA [20].…”
Section: Discussionmentioning
confidence: 99%
“…These results may explain the link between SUA levels and depressive symptoms in PWE. Considering these findings, epileptic seizure and SUA affect each other, and the interaction is responsible for the development of epilepsy [19]. Given that lowered SUA levels have also been observed in depression and anxiety disorders, there may be a complex relationship between SUA, mental illness and epilepsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) Previous studies have shown that UA may be related to the size, type, and location of cerebral infarction [ 5 , 27 ]. Studies have suggested that UA levels may be associated with secondary epilepsy following cerebral infarction [ 28 ], but these data were not collected in this study. (4) Patients with cerebral infarction may also have Parkinson's disease, decreased cognitive function, or other chronic diseases, which may also be related to UA levels.…”
Section: Discussionmentioning
confidence: 99%